HD 28109 hosts a trio of transiting Neptunian planets including a near-resonant pair, confirmed by ASTEP from Antarctica. Issue 1 (22nd July 2022) - Dransfield, Georgina; Triaud, Amaury H M J; Guillot, Tristan; Mekarnia, Djamel; Nesvorný, David; Crouzet, Nicolas; Abe, Lyu; Agabi, Karim; Buttu, Marco; Cabrera, Juan; Gandolfi, Davide; Günther, Maximilian N; et al.
ABSTRACT: We report on the discovery and characterization of three planets orbiting the F8 star HD 28109, which sits comfortably in TESS 's continuous viewing zone. The two outer planets have periods of 56.0067 ± 0.0003 d and 84.2597_-0.0008^+0.0010 d, which implies a period ratio very close to that of the first-order 3:2 mean motion resonance, exciting transit timing variations (TTVs) of up to 60 min . These two planets were first identified by TESS, and we identified a third planet in the TESS photometry with a period of 22.8911 ± 0.0004 d . We confirm the planetary nature of all three planetary candidates using ground-based photometry from Hazelwood, ASTEP, and LCO, including a full detection of the 9 h transit of HD 28109 c from Antarctica. The radii of the three planets are R_b=2.199_-0.10^+0.098 R_, R_c=4.23± 0.11 R_, and R_d=3.25± 0.11 R_ ; we characterize their masses using TTVs and precise radial velocities from ESPRESSO and HARPS, and find them to be M_b=18.5_-7.6^+9.1 M_, M_c=7.9_-3.0^+4.2 M_, and M_d=5.7_-2.1^+2.7 M_, making planet b a dense, massive planet while c and d are both underdense. We also demonstrate that the two outer planets are ripe for atmospheric characterization using transmission spectroscopy, especially given their position in the CVZ of James Webb Space Telescope . The data obtained to date are consistent with resonant (librating) and non-resonant (circulating) solutions; additional observations will show whether the pair is actually locked in resonance or just near-resonant.